1995
DOI: 10.1002/jlb.58.5.575
|View full text |Cite
|
Sign up to set email alerts
|

A novel biological effect of platelet factor 4 (PF4): enhancement of LPS-induced tissue factor activity in monocytes

Abstract: In a previous study we have shown that granulocytes enhance lipopolysaccharide (LPS)-induced tissue factor (TF) activity in monocytes in a platelet-dependent reaction. The present investigation was undertaken to examine the role of a platelet activation product, platelet factor 4 (PF4), in LPS-induced TF activity in monocytes. Platelet lysate supernatant, purified PF4, and the COOH-terminal tridecapeptide of PF4, termed PF4(58-70), enhanced LPS-induced TF activity in monocytes of whole blood dose dependently. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(50 citation statements)
references
References 0 publications
1
49
0
Order By: Relevance
“…Thus, although P-selectin-expressing platelets may not induce tissue factor (TF) expression on monocytes (Weyrich et al, 1996), as suggested by others (Celi et al, 1994), a P-selectin-and PF4-dependent interaction among activated platelets, granulocytes and monocytes augments lipopolysaccharide-induced TF expression on monocytes (Engstad et al, 1995). Consequently, in an inflammatory event, TF expression on monocytes may be disproportionately expressed in MPD patients, resulting in activation of the coagulation protease cascades via TF binding to factor VII/VIIa.…”
Section: Discussionmentioning
confidence: 98%
“…Thus, although P-selectin-expressing platelets may not induce tissue factor (TF) expression on monocytes (Weyrich et al, 1996), as suggested by others (Celi et al, 1994), a P-selectin-and PF4-dependent interaction among activated platelets, granulocytes and monocytes augments lipopolysaccharide-induced TF expression on monocytes (Engstad et al, 1995). Consequently, in an inflammatory event, TF expression on monocytes may be disproportionately expressed in MPD patients, resulting in activation of the coagulation protease cascades via TF binding to factor VII/VIIa.…”
Section: Discussionmentioning
confidence: 98%
“…Unlike PBP and other chemokines, PF4 appears to bind mostly to large, negatively charged molecules such as heparin, and though many biologic functions have been attributed to PF4, its true role in vivo is unknown. [6][7][8][9] Although the biologic roles of these chemokines need further investigation, their genes offer an opportunity to understand megakaryocyte-specific expression. Like many other genes encoding chemokines, both the PBP and PF4 genes are encoded by 3 exons, and are preceded by a TATA box in the immediate 5Ј-flanking region.…”
mentioning
confidence: 99%
“…The extrinsic pathway is initiated by tissue factor (TF). TF is a transmembrane glycoprotein constitutively expressed on extravascular cells (like fibroblasts and pericytes surrounding blood vessels), while inducible expressed upon blood vessel injury [41,42], as well as in monocytes upon stimulation with LPS or bacteria's [43][44][45]. TF is also exposed on circulating cell-derived microparticles (MPs) [46].…”
Section: Whole Blood Effector Systemsmentioning
confidence: 99%